(untitled) (International Seven Journal of Health Research, 2025)
Heart diseases represent a worrying condition in ICU patients, and heart failure (HF) is one of the most common and aggravating heart diseases, as it compromises respiratory function. HF causes the accumulation of fluids in the lungs, generating pulmonary edema and, consequently, atelectasis, which collapses the alveoli. This collapse reduces gas exchange, aggravating hypoxemia and making it difficult for the patient to recover. Due to the importance of the theme, the study aims to identify how alveolar recruitment maneuvers can help in the treatment of patients in cardiology ICUs. A search for scientific articles was carried out in the PubMed, SciELO, Getinge, Artmed and ScienceDirect databases. Articles published in full, in English and Portuguese, that addressed cardiology ICU patients on mechanical ventilation after cardiac surgery, patients affected by ARDS, and ICU patients in whom alveolar recruitment maneuvers were adopted as a therapeutic measure were included in the search. Studies that did not use alveolar recruitment maneuvers as an intervention method were excluded. Alveolar recruitment maneuvers, associated with pulmonary protective ventilation strategies, can establish a good hemodynamic condition, reducing lung lesions and significantly increasing oxygenation levels.